Online Counseling in Improving Achievement Motivation Over the Last Decade: A Bibliometric Review - Kurniawan, Shopyan Jepri; Wiyono, Bambang Dibyo; Zulazmi, Mohd. Aziz (Jurnal Kajian Bimbingan dan Konseling, 2025)
This research aims to determine online counseling research trends to increase achievement motivation. The method used in this research is bibliometric analysis using VOSviewer. The data used is the Scopus database for the last 10 years. Research findings found that there were 4302 documents that met the specified criteria. The number of online counseling studies increased gradually over the 2013-2022 research period. The largest source of documents comes from 3691 articles. Meanwhile, the annual distribution of 100 or more citations will be the highest in 2022 with 16. The keyword ``achievement motivation'' is not included in the top 10 keywords, this shows that there is no research on online counseling to increase students' achievement motivation. This condition opens up opportunities for further research related to online counseling to increase student achievement motivation.